Long non-coding RNA LINC01268 promotes cell growth and inhibits cell apoptosis by modulating miR-217/SOS1 axis in acute myeloid leukemia - Chen,Beili (2020)
The aim of this study was to evaluate the pathogenic role of newly identified long non-coding (lnc)-RNA LINCO1268 in acute myeloid leukemia (AML), and investigate its therapeutic potential. The expression level of LINC01268 in AML was measured by quantitative PCR (qPCR). The viability, cell cycle progression, and apoptosis of AML cells were measured by CCK-8 assay and flow cytometry, respectively. The interaction between LINC01268 and miR-217 were predicted by the miRDB website, and then verified by luciferase reporter assay and RNA immunoprecipitation (RIP) assay. The relationship between miR-217 and SOS1 was predicted by TargetScan website, and verified by luciferase reporter assay. LINC01268 was significantly upregulated by 1.6 fold in bone marrow samples of AML patients, which was associated with poor prognosis. LINC01268 was also significantly upregulated in AML cells. LINC01268 knockdown inhibited viability and cell cycle progression but promoted apoptosis of AML cells. Furthermore, LINC01268 functioned as a ceRNA via competitively binding to miR-217, and SOS1 was identified as a target of miR-217. Moreover, LINC01268 positively regulated SOS1 expression to promote AML cell viability and cell cycle progression but inhibited apoptosis via sponging miR-217. LINC01268 promoted cell growth and inhibited cell apoptosis through modulating miR-217/SOS1 axis in AML. This study offers a novel molecular mechanism for a better understanding of the pathology of AML. LINC01268 could be considered as a potential biomarker for the therapy and diagnosis of AML.